Digital health : mobile and wearable devices for participatory health applications - Syed-Abdul, Shabbir; Zhu, Xinxin; Fernandez-Luque, Luis (Elsevier, 2021)
Digital Health: Mobile and Wearable Devices for Participatory Health Applications is a key reference for engineering and clinical professionals considering the development or implementation of mobile and wearable solutions in the healthcare domain. The book presents a comprehensive overview of devices and appropriateness for the respective applications. It also explores the ethical, privacy, and cybersecurity aspects inherent in networked and mobile technologies. It offers expert perspectives on various approaches to the implementation and integration of these devices and applications across all areas of healthcare. The book is designed with a multidisciplinary audience in mind; from software developers and biomedical engineers who are designing these devices to clinical professionals working with patients and engineers on device testing, human factors design, and user engagement/compliance.